EUFEMISME DALAM BAHASA INGGRIS DAN BAHASA TONTEMBOAN: SUATU ANALISIS KONTRASTIF - SUPIT, JULITA VERONICA; RATTU, JULTJE A.J.; PAMANTUNG, RINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
Â ABSTRACTThis research is entitled â€œEuphemism in English and Tontemboan Language: A Contrastive Analysisâ€. The objectives of this research are to identify and classify the forms of euphemism and to analyze and describe the differences of euphemism in English and Tontemboan language. This research uses a descriptive method. There are three steps to finish this research, those are preparation, data collection, and to analyze and describe the data that using the theory of Fromkin (1997: 286), Wardhaugh (1986: 231), and Allan and Burridge (1991: 14), and were contrasted to find the differences using Ladoâ€™s theory. The result of this research shows that form of euphemism in Tontemboan language more shows a stress in a word or sentence than form of euphemism in English. There are 79 euphemisms found in English and 48 euphemisms in Tontemboan language. The euphemism in English were classified into 23 forms those are: sex, the part of human body, natural function of body, religion, dying, unemployment, criminality, figurative expression, flippancy, remodelling, circumlocution, clipping, acronym, abbreviation, omission, one for one substitution, general for specific, part for whole euphemism, hyperbole, understatement, use of technical terms of jargon, use of general or colloquial terms, and methapor. In Tontemboan language, there are some forms of euphemism that were not found those are: flippancy, remodelling, circumlocution, acronym, abbreviation, part for whole euphemism, use of technical terms or jargon. In this research, especially in Tontemboan language there is one form of euphemism that the writer found that was not included in three concepts used, namely euphemism related to supernatural.Â Keywords: Euphemism, English and Tontemboan Language, Contrastive Analysis